In vitro compatibility of natural and food grade fungicide and insecticide substances with Purpureocillium lilacinum and their effect against Aspergillus flavus - Barra, Paula Sabina (2013)
The objective of our study was to evaluate the compatibility of 21 Purpureocillium lilacinum strains with two benzoic acids 2(3)-tert-butyl-4 hydroxyanisole (BHA) and 2,6-di(tert-butyl)-p-cresol (BHT) and two phenolic acids 3-phenyl-2-propenoic acid (CA) and trans-4-hydroxy-3-methoxycinnamic acid (FA) applied alone or in combination, at different water activities. The impact of chemical substances and entomopathogenic fungi combination on growth parameters and toxin production of Aspergillus section Flavi in vitro was analyzed. BHT, the mixture BHA + BHT, CA and BHA did not significantly influence the count of viable spores of the 21 P. lilacinum strains. The strains JQ926202 and JQ926222 showed compatibility with the four treatments evaluated. The 21 P. lilacinum strains and the mixture of these entomopathogenic fungi with BHA (1 mM) increased the lag phase and inhibited the growth rate and aflatoxin B1 production of Aspergillus flavus at three aw assayed.